Tracking the origin and dispersal of the Asian chestnut gall wasp Dryocosmus kuriphilus Yasumatsu (Hymenoptera, Cynipidae) in Europe with molecular markers. Issue 3 (1st October 2018) - Martinez-Sañudo, I.; Mazzon, L.; Simonato, M.; Avtzis, D.; Pujade-Villar, J.; Faccoli, M.
Abstract: The Asian chestnut gall wasp, Dryocosmus kuriphilus, is an invasive pest causing significant damage to chestnut trees ( Castanea spp., Fagaceae). Originating from China, it has recently invaded a wide range of regions in Europe and North America. Understanding the population genetic structure of important invasive pests is very useful for improving the knowledge concerning routes of expansion and colonizing capacity. Despite its economic importance, limited attention has been given to D. kuriphilus origin and spread, or to its genetic structure. In this study, D. kuriphilus populations sampled in eight European countries were screened using both mitochondrial (cytochrome c oxidase subunit 1; COI) and nuclear (internal transcribed spacer 2; ITS2) sequences, and Amplified Fragment Length Polymorphism (AFLP) markers. The molecular markers COI and ITS2 highlighted the presence of a single haplotype in all the studied populations. The recorded mitochondrial haplotype was identical to one of the most widespread haplotypes occurring in the native area (China). AFLP results indicated that D. kuriphilus individuals belong to two genetically distinct clusters without any further geographic clustering. These results suggest that D. kuriphilus populations in Europe could be the result of a single introduction of a Chinese founder population characterized by two genetically distinct lineages that subsequently spread rapidly across Europe. However, the possibility that populations originated from multiple introductions of the same Chinese mitochondrial haplotype cannot be excluded. The reported results provide useful information concerning this invasive species, potentially facilitating integrated pest management.